The medium-term outlook and choices - Bee Boileau; David Phillips; Sam Ray-Chaudhuri; Tom Waters (Institute for Fiscal Studies (IFS), 2024)
This chapter of our second annual Budget Report looks beyond 2024-25 to the medium-term outlook for the Scottish Government's funding, and the implications of the funding picture for the choices and trade-offs faced when allocating funding between areas of the budget. The Scottish Government had said it would confront those choices alongside the 2024-25 Budget by publishing an update to 2022's Resource Spending Review. However, with the Deputy First Minister and Finance Minister, Shona Robison, citing the 'turbulent economic environment', a decision has been taken to postpone this until the next set of economic and fiscal forecasts from the Scottish Fiscal Commission (SFC) and the publication of the next Scottish Government Medium-Term Financial Strategy (MTFS), expected in the late spring or early summer. Our analysis, presented below and based on current forecasts for UK government funding and devolved tax revenues, suggests that 2025-26 will see a substantial real-terms increase in Scottish Government resource funding. However, 2026-27 onwards is currently forecast to see much smaller increases in resource funding - that could easily be more than entirely absorbed by the NHS and other priority areas, necessitating cutbacks to many other services. A planned cashterms freeze to capital funding from the UK government, together with Scotland planning to reduce borrowing used for capital purposes (in an attempt to maintain some headroom against its borrowing limits), is set to see capital funding in Scotland fall significantly in real terms over the second half of the 2020s. More funding than is currently pencilled in might be made available by the UK government for both resource and capital purposes, but risks to net revenues from devolved taxes are likely weighed to the downside. The Scottish Government should not bank on significantly more funding becoming available.
Keywords: 330; Government finances and spending; Health and social care; Taxes and benefits; Scottish Budget 2024-25; Benefits; Devolved government finances; Government spending; Healthcare; Income taxes; Local government finance; Property taxes; Public finance; Public sector; Tax; Working age benefits; Scotland